THE EFFECTIVENESS OF PROBLEM-BASED LEARNING IN STUDENTS’ LISTENING SKILL IN TOEIC OF LISTENING MATERIALS AT INDONESIAN ACADEMY OF SECRETARY AND MANAGEMENT CITRA NUSANTARA - Bahing Siritman,; Mayang Meilantine, (Journal of Innovation Research and Knowledge, 2025)
This research was highly concerned with the study of Problem-based learning in listening materials. This aimed at finding out whether or not problem-based learning could be developed to strengthen students’ listening skill. This research was an experimental one, which aimed to find out the effect of using Problem-based learning method to increase students’ listening skill. The population of this research was the sixth semester students of Indonesian academy of secretary and management Indonesi (ASMI) Citra Nusantara Banjarmasin. Sample were students majoring Financial Management 1 as control group. It was obtained by using purpose sampling technic. Experimental group was taught by using Problem-based Learning method which consisted of 22 students. While control group was taught by using conventional method consisted of 23 students. The instrument of this research was TOEIC of listening comprehension Test. Problem-based Learning method was more effective to increase students’ Listening skill at Indonesia Academy of Secretary and management of Indonesia (ASMI) Citra Nusantara Banjarmasin than the conventional method. It was indicated by the result of independent sample of T-test, and it was found Significant. Tail 2 value was 0,000< 0,05. It meant there was significant different in students’ listening skill between Experimental Group and the Control Group. In group statistics table said that the mean of experimental group was 275,91. It was higher than the mean of control group 194,7. It could be stated that Ho was rejected, and ha was accepted. In other words, Problem-based learning method in teaching listening skill could developed the students’ listening skill better than the conventional one.